(3GdCSWQfhejGs
(3ChdgG (B:s
(3EYde CjgG GdCN GdHGQ GdQMje HCf Yde GdfLhe jfbSe KdGKI CfhGY (B: (3fhY efgG eYQaI GdCadGc hcejI GdchGcH , hCbSGe GdHQhL hCHYGOgG hYXeJgG hMQcJgG heGjJHYgG ef gPG Gdaf s
(3BNQgG (B:s
(3GdchcH EPG cGf ai GdKGef ef GdWGdY de jbSe NjQkG hdG TQkG hGdfMhS jYXe TQgG JeJ GdQSGdI GdedbHI HGdCTWQfhejG hgj GdeONd Edi Yde GdfLhe , ef QSGFd ENhGf GdUaG hNdGf GdhaG JeJ HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B152 - (3U(B183s
(3HgG fXGe GdJYbjHIs
(3HgG QShe hCTcGds
(3hgh GdeONd Edi Yde GdfLhe (B: (3ef QSGFd ENhGf GdUaG hNdGf GdhaG hcdeI GdCSWQfhejG cdeI jhfGfjI GdCUd JYfi Yde GdfLhes
(3cJHJ Hbde VHWI bdjd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdadcs